An example for a one-parameter nonexpansive semigroup. (28th April 2005) - Suzuki, Tomonari
Abstract : We give one example for a one-parameter nonexpansive semigroup. This example shows that there exists a one-parameter nonexpansive semigroup T ( t ) : t ≥ 0 on a closed convex subsetC of a Banach spaceE such thatlim t → ∞ ‖ ( 1 / t ) ∫ 0 t T ( s ) x d s − x ‖ = 0 for somex ∈ C, which is not a common fixed point of T ( t ) : t ≥ 0 .